Pengaruh Jenis Sensor Water Level dan Variasi Tegangan Terhadap Ketinggian Air Pada Tangki Bensin Berbasis Arduino - Yuniarto Agus Winoko; Moch Riduwan (Universitas Muhammadiyah Metro, 2026)
Cases of vehicle tank leaks throughout 2024-2025 amounted to 23,500 units. The cause of vehicle tank leaks is water vapor (condensation) because the empty space in the tank contains air. Water Level Sensor is a sensor used to detect and measure water levels. The way the Water Level Sensor works by utilizing an open conductor path that is connected when in contact with water, the Water Level Sensor used is HW 37 and HW 38. The purpose of this study is to determine the effect of the type of Water Level Sensor HW 37 and HW 38, variations in working voltage of 3V and 5V and to compare the percentage error value of water level measurements of 5, 10, 15 and 20 mm. The test method uses experiments presented in the form of tables and graphs. The independent variables are the type of sensor and voltage. The dependent variables are the accuracy of water level measurements of 5, 10, 15, and 20 mm. The test results of the Water Level Sensor HW 37 with the best accuracy occurred at a voltage of 5V with a percentage error value of 0.35%, while the Water Level Sensor HW 3 with the best accuracy occurred at a voltage of 5V with a percentage error value of 0.10%.